Effective non-invasive runway monitoring system development using dual sensor devices - Sharma, R. (2022)
At airports the runways are always troubled by the presence of ice, water, cracks, foreign objects, etc. To avoid such problems the runway is supposed to be monitored regularly. To monitor a large number of technique are available such a runway inspection mobile vans. These techniques are largely human dependent and need interruptions in the runway’s operations for inspection. In this position paper, we suggest an alternative way to monitor the runway. This method is non-invasive in nature with the involvement of Light Detection and Ranging (LIDAR) sensors. In the methodology, we describe the schemes of labelling the data obtained from LIDAR using a MARWIS sensors fitted in a mobile van. We describe the entire system and the underlying technology involved to develop the system. The proposed system has the potential of developing an efficient runway monitoring system because the LIDAR technology has proved its efficiency in several terrestrial mapping and monitoring system.